OPTIMIZATION OF CUTTINGS TRANSPORT IN VERTICAL, INCLINED AND HORIZONTAL SEGMENTS OF THE WELL - EBRAHIM MOHAMMED, NUHA HUSSEIN (2015)
Transportation of drill cuttings is affected by drilling mud velocity profile and the position of the drill pipe in the well. Drilling mud velocity varies across the annulus, from zero value at the boundaries, to maximum value at the middle; and for any degree of eccentricity, the flow profiles would change. In this case mean velocity cannot predict adequately the cuttings behavior. Researchers have investigated the etTect of eccentricity on annular velocity profile and have shown it to have major impact. However, the effect of the variation in annular geometry in the annular flow behavior, and in turn the drill cuttings flow behavior has not been properly studied. The objective of this study is to investigate the effect of differential flow profile in cuttings transport modeling. Governing equations for Newtonian and non-Newtonian (power-law) fluids flow in eccentric (offset between the centers of the drill pipe and well bore) annulus are developed using bipolar coordinates system.